Hubungan Manajemen Sistem Informasi dengan Kinerja Guru di SD Negeri Kelurahan Tanah Tinggi Jakarta Pusat - Elan Suherlan; Mukhneri Mukhtar; Eliana Sari (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2016)
This study aims to determine Relationship Management Information Systems with Elementary School Teacher Performance in Central Jakarta Sub Highlands. The sample in this study were teachers Highlands Village SDN 75 people. Proportional sampling using sampling. The method used was survey method with the correlational approach. The data collection was done by distributing questionnaires and analyzed using Normality Test and Test of Significance analysis technique Product Moment and conclusions with Hypothesis Testing. The results showed that the positive effect of management information systems with the performance of primary school teachers in the village of Highlands, Central Jakarta. These results indicate that management information systems can be used as one of the efforts to improve the performance of primary school teachers in the village of Highlands, Central Jakarta. Therefore, teachers need to know about the system implemented in the school as well as the delivery of accurate information from the school to the teacher. Facilities required to meet the school does in IT so that classroom teaching and learning activities designed by teachers varied, in order to improve teacher performance.